2017
DOI: 10.4236/ajps.2017.85065
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemicals as Growth Stimulators for Drought Stressed Maize

Abstract: Sorgaab, an aqueous extract of sorghum leaves was applied to probe the modulation in growth and physiological attributes of maize under drought in lab and greenhouse studies. Sorgaab soaked seeds (10 dilutions) were germinated to assess drought tolerance at germination and seedling growth stages. More concentrated Sorgaab solutions (2 mL•L −1 ) were damaging, while lower concentration in the range of 0.75 to 1.5 mL•L −1 improved the root and shoot growth of maize under drought. Applied drought stress decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Result of combined analysis (Table 5 a,b) showed that under normal irrigation condition, plant height, ear diameter, ear length, number of rows/ ear, number of grains/row, ear weight, ear grain weight, 100 grain weight and grain yield were significantly more than drought stress condition at both seasons. Several researchers reported that maize yield decreased under water or drought stress condition (Daryanto et al 2016 andMaqbool andSadiq, 2017). In this experiment, grain yield augmented from 2993.2kg ha -1 at a level of 50 % of water requirements to 4646.6kg ha -1 at a level of 75 % of water requirements and to 6167kg ha -1 under a level of 100 % of water requirements in the first season.…”
Section: In Vivo Mesurment Of Maize Growth and Yield Prametersmentioning
confidence: 70%
“…Result of combined analysis (Table 5 a,b) showed that under normal irrigation condition, plant height, ear diameter, ear length, number of rows/ ear, number of grains/row, ear weight, ear grain weight, 100 grain weight and grain yield were significantly more than drought stress condition at both seasons. Several researchers reported that maize yield decreased under water or drought stress condition (Daryanto et al 2016 andMaqbool andSadiq, 2017). In this experiment, grain yield augmented from 2993.2kg ha -1 at a level of 50 % of water requirements to 4646.6kg ha -1 at a level of 75 % of water requirements and to 6167kg ha -1 under a level of 100 % of water requirements in the first season.…”
Section: In Vivo Mesurment Of Maize Growth and Yield Prametersmentioning
confidence: 70%
“…Maize seedlings treated with plant extracts derived from red grape, blueberry fruits, and hawthorn leaves showed increased root and leaf biomass, chlorophyll and sugar content, as well as phenolic acids compared to untreated plants (Ertani et al 2016). Recently, a positive effect against drought stress was also observed in maize treated with an aqueous extract of sorghum leaves (Maqbool and Sadiq 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Plants are sessile and often are exposed to various abiotic stresses, such as heat and drought, either individually or in combination, adversely affecting plant growth, development, and productivity [ 4 ]. Drought is a meteorological condition where the plants receive inadequate rainfall and often show a high evapotranspiration rate and low water-holding capacity around the rhizosphere [ 4 , 5 ]. Drought can influence plants' molecular, biochemical, and physiological processes, resulting in yield loss [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drought is a meteorological condition where the plants receive inadequate rainfall and often show a high evapotranspiration rate and low water-holding capacity around the rhizosphere [ 4 , 5 ]. Drought can influence plants' molecular, biochemical, and physiological processes, resulting in yield loss [ 4 , 5 ]. Heat stress is often referred to as a condition when plants are exposed to excessive air temperatures for prolonged periods [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%